2006
DOI: 10.1007/s11270-005-9068-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bayesian Regularized BP Neural Network Model for Trend Analysis, Acidity and Chemical Composition of Precipitation in North Carolina

Abstract: Bayesian regularized back-propagation neural network (BRBPNN) was developed for trend analysis, acidity and chemical composition of precipitation in North Carolina using precipitation chemistry data in NADP. This study included two BRBPNN application problems: (i) the relationship between precipitation acidity (pH) and other ions (NH + 4 , NO − 3 , SO 2− 4 , Ca 2+ , Mg 2+ , K + , Cl − and Na + ) was performed by BRBPNN and the achieved optimal network structure was 8-15-1. Then the relative importance index, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…That is, in contrast to conventional network training where an optimal set of weights is chosen by minimizing an error function, the Bayesian approach involves a probability distribution of network weights. As a result, the predictions of the network are also a probability distribution [19,20].…”
Section: Solution To the Overfitting Problem With Bayesian Regularizamentioning
confidence: 99%
“…That is, in contrast to conventional network training where an optimal set of weights is chosen by minimizing an error function, the Bayesian approach involves a probability distribution of network weights. As a result, the predictions of the network are also a probability distribution [19,20].…”
Section: Solution To the Overfitting Problem With Bayesian Regularizamentioning
confidence: 99%
“…Facing with the dynamic, nonlinear, and uncertain characteristics of soil properties in the complex ecosystem, a recent approach to model PTFs is to use an artificial neural network (ANN). Most researchers have found that ANN performs better than multiple linear regressions (MLRs), with no specific function of relationship to be assumed beforehand, capable of predicting large quantities of complex soil properties precisely that encompass most soils in a survey area (Minasny and McBratney, 2002;Minasny et al, 2004;Tang et al, 2006;Xu et al, 2006). Radial basis function neural network (RBFN) is an important model of feedforward neural networks with a single hidden layer and a linear output layer (Panagou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…AHP is appropriate for regional management and planning as it can accommodate conflicting, multi-dimensional, incommensurable, and incomparable set of objectives [131]. Taking sustainability into account, this technique involves the paired comparisons of socio-economic objectives that are considered to be as important as eco-political aspects [133,134]. While AHP is an important member of a general family of multi-criteria decision making, which helps to combine the information from various criteria into a single index of evaluation, RS and GIS can capture a wide range of criteria data that are derived from different multi-spatial, multi-temporal, and multi-scale sources for a time-efficient and cost-effective analysis.…”
Section: Land For Food Production and For Infrastructurementioning
confidence: 99%